'Living to tell the tale' — Narratives of Surviving Cancer and the Social Work Response. Issue 2 (2nd April 2016) - Taplin, Sue
Abstract : This article draws on themes derived from research conducted as part of my doctoral study with eighteen individuals who were living with cancer, in which they were invited to explore the ways in which they experienced the world around them, how it had affected their sense of self and their relationships with others and whether and in what ways it had given them a different perspective on the present and the future. This research developed from my practice as a Social Worker in Palliative Care, during which time I became fascinated by the different reactions and responses which individual people displayed to a diagnosis of life-threatening illness, and how these changed during the trajectory of the illness, and specifically, in people living with a diagnosis of cancer, which did not always result in death. Drawing on interviews with cancer 'survivors', the concepts of biographical disruption, liminality and survivorship are explored as a means of understanding the reality of living with cancer. Finally there is a discussion of the implications of the research for contemporary social work practice.